(untitled) (Práxis Educativa, 2024)
Purpose of this study is the attitudes of students before the service for pedagogical practice in study program Preschool Education and Primary Education. Since the scope of these programs within the Faculties of Education has the mission of teaching. Research was carried out using the qualitative method, instrument for realization of the research was a semi-structured interview with a total of 15 students of these programs for pedagogical practice. Through reviewed literature and qualitative research, we have obtained results that pedagogical practice is useful and prepares students to be ready for service after graduation, also mentor teachers at school as well as supervising professors make an extraordinary contribution to the professional development of students before the service. To conclude, we have extracted the attitudes of students about importance of practical learning, students from pedagogical practice in educational institutions have benefited from experiences related to cooperation, planning, inclusiveness, plan realization, and should use these potentials for benefits of them regarding preparation for teachers in the future. Research is of particular importance in the field of education, serves students of Faculties of Education, teachers, professors of higher education, and as such is useful for sciences of Education in general. Keywords: Teacher training. Pedagogical practice. Faculty of Education.